Contribution of seven legumes residues incorporated into soil and NP fertilizer to maize yield, nitrogen use efficiency and harvest index in degraded soil in the center of Benin - KOUELO ALLADASSI, FÉLIX; HOUNGNANDAN, PASCAL; GERD, DERCON (My University, 2013)
A field experiment evaluated the impact of seven legumes cover crops residues incorporated into degraded soil (Aeschynomene histrix, Centrosema pubescens, Chamaecrista rotundifolia, Mucuna pruriens, Pueraria phaseoloïdes, Stylosanthes guianensis and S. Hamata) on maize yield, N uptake and harvest index in the center of Benin. In July 2003, the cover crops were planted and received two level of phosphorus (45 P and 0 P) applied in form of Super Phosphate Triple. In May 2004, two split of nitrogen were added on the residues of the legumes, 30 days after the planting of maize. Minerals fertilizers (N, P) enhanced maize yield, N uptake, harvest index and N use efficiency. Incorporation of legumes residues improved more maize productivity than minerals fertilizers. The best grain yield (1793.9 kg DM.ha-1) and grain N uptake (149.4 kg N ha-1) were obtained with Mucuna pruriens residues incorporated. The combination of N and P to the different residues didn’t improve significantly the maize yields. The maize grain yield is explained to 90% by biomass, harvest index and nitrogen use efficiency. The proportion of explained grain N uptake in biomass, harvest index and nitrogen use efficiency is 74%. The results demonstrated that growing maize with Mucuna pruriens residue incorporation with NP fertilizers could be more beneficial in the legume-maize cropping system in the study area
Keywords: Crop residues; mineral fertilizers; maize yield; NUE; degraded soil